FSKM directory map system / Amir Irsyad Roslan - Roslan, Amir Irsyad (2016)
FSKM Directory Map System is a project that is use to help user to reach their destination in the Faculty of Computer and Mathematical Sciences in an effective way, the main target audience of this project are students from Faculty of Computer and Mathematical Sciences. Previously, the user either students or visitors always take long time to search for rooms and offices at the faculty. They also found that there is too much information at the directory map board that is placed at the foyer. The development of this project is based on waterfall model by using 2D and 3D modeling. The significant of the study are the user can get the best route to the destination and save the user time to reach their destination. 8 respondents have been selected for user satisfaction test that consists of two lecturers and six students from Faculty of Computer and Mathematical Sciences. Majority of the respondents agreed that this system can replace the current system that currently being used at the faculty.